3 (15-6)+(18-12)^2=
3 (9) + (6)^2=
27 + 36 =
63
Answer:
6
because when you subtract 6 from 6 you get 0
6 - 6 = 0
Answer:c,d,f I think
Step-by-step explanation:
9514 1404 393
Answer:
3
Step-by-step explanation:
The gradient is the ratio of "rise" to "run". Here, it appears the line crosses the y-axis at y = -1. It appears that it also crosses the grid intersection at (1, 2). This represents a "rise" (change in y) of (2 -(-1)) = 3, for a "run" (change in x) of (1 -0) = 1. Then the gradient is ...
m = rise/run = 3/1 = 3
The gradient of the graph is 3.